WHY IS SPIRITUALITY MARGINALIZED? CRITIQUE ON NEW DEFINITION OF HEALTH IN THE MODERN MEDICINE - Ahmad Kalateh Sadati (ISSUE: Journal of Islamic Studies for Universal Dialogue, 2024)
New definition of health includes spiritual aspect of human being as an important dimension. In this approach, health defined as a bio-psycho-socio-spiritual phenomena so that if all of these dimensions are in a normal condition then we can say a person is healthy. In this framework, spiritual dimension as an ignored aspect is scrutinized. Although this approach is a step forward about definition of health, but it includes some defects. This is due to the modern wisdom that has penetrated into medicine; in turn, any illnessess was managed into secular context. Due to this, the totality of spirituality as a main dimension of human being reduced to one of its function that is related to its role in physical and psychological health. So, ontological dimension of spirituality was declined into limited function. In this reductionism, spirit ignored and medicine focuses on the limited role of spirituality in health. Because of this, medicine confronts with these problems: 1. It doesn’t pay any attention to the human beings and his/her dependency to the cosmic order; 2. Medicine is more functional than relational so, that the importance of spirituality is due to its function not to its relations with the human beings and his/her interpretation of cosmic order; 3. Despite the acceptance of spiritual dimension, medicine likewise is one-dimensional. This one-dimensional approach leads to many failures in diagnosis and treatment; and 4. Due to its secular context, modern medicine doesn’t pay any attention to totality of spirit that called human soul. As a proposed model, Islamic view has holistic approach that its' definition of health is in relation with the Ultimate Reality and his Will. This paper is a documented study to evaluate the above characteristics.